SINDROM PICKWICKIANSINDROM HIPOVENTILASI PADA OBESITAS LAPORAN KASUS DENGAN PENDEKATAN DIAGNOSIS KLINIS - Ni Luh Putu Dirasandhi Semedi Putri,* Desak Ketut Indrasari Utami,* I Gusti Ngurah Budiarsa,* Sri Ye (Neurona Majalah Kedokteran Neuro Sains, 2019)
36YEAROLD MAN COMPLAINED ABOUT SNORING IN THE PAST 3 YEARS WITH A VERY LOUD SNORING INTERSPERSED WITH CHOKING THIS RECURS THROUGHOUT THE NIGHT THUS HE OFTEN EXPERIENCES EXCESSIVE DROWSINESS DURING THE DAY HE ALSO EXPERIENCED GENERALIZED TONICCLONIC SEIZURE IN THE PAST SIX MONTHS DURING SLEEPING AT NIGHT OR IMMEDIATELY AFTER WAKE UP IN THE MORNING IT HAPPENED THREE TO FOUR TIMES A WEEK IN THE PAST ONE MONTH HE ALSO EXPERIENCED A MORNING HEADACHE HE WAS CLASSIFIED AS MORBID OBESITY AND HAD 472 CM WIDE OF NECK CIRCUMFERENCE